Magneto-hydrodynamic behavior of magnetic nanofluids in mini-channel heat sinks for electronics cooling - Suvanjan Bhattacharyya; Nada Al Taisan; Sumit Khatri; Basma Souayeh; Huda Alfannakh; Devendra Kumar Vishwakarma (Scientific Reports)
Abstract The rapid advancement of high-density electronic devices and data centres has heightened the demand for effective thermal management solutions capable of handling elevated heat fluxes within compact domains. Conventional cooling techniques often fail to meet these requirements efficiently. This study presents a numerical investigation of heat transfer enhancement in a mini-channel heat sink through the combined use of passive vortex generators (ribs) and externally applied magnetic fields. A two-dimensional simulation was conducted for a 40 mm × 4 mm mini-channel employing a 2% Fe3O4–water nanofluid, with magnets positioned at X = 15 mm and X = 25 mm to generate non-uniform magnetic fields ranging from 800 to 2000 G. Three rib configurations parallel, staggered, and ribbed were evaluated across a Reynolds number range of 50, 75, 100, 150, 180, and 210. Results indicate that the ribbed configuration provides the highest heat transfer improvement, achieving up to a 65% increase relative to the baseline, while the parallel arrangement attained the highest absolute Nusselt number. The friction factor increased with stronger magnetic fields but decreased with higher Reynolds numbers. The thermal enhancement factor remained consistently above unity, with peak values of 2.06 for ribbed, 1.77 for parallel, and 1.52 for staggered layouts. Overall, this study demonstrates that integrating rib-induced vortex generation with magnetic field effects offers a promising strategy for enhancing the thermal performance of mini-channel heat sinks, addressing the cooling demands of next-generation electronic and data centre applications.